The Boy Scouts Along the Susquehanna; or, The Silver Fox Patrol Caught in a Flood - Carter, Herbert, active 1909-1917 (Salt Lake City, UT : Project Gutenberg, 2014)
"The Boy Scouts Along the Susquehanna; or, The Silver Fox Patrol Caught in a Flood" by Herbert Carter is a children$1 (Bs adventure novel written in the early 20th century. The story follows a group of Boy Scouts, particularly the Silver Fox Patrol, led by Thad Brewster, as they embark on a quest to recover an old army coat that contains a valuable document. Their journey unfolds with a mix of excitement, challenges, and the spirit of camaraderie as they explore the great outdoors and encounter various obstacles along the Susquehanna River. The opening of the narrative introduces the boys during a rest on their hike, discussing weather predictions and their gear. Thad Brewster has organized this expedition not only for fun but also to investigate the whereabouts of the army coat lost to a hobo named Wandering George, who is suspected of having a connection to an important story involving Thad's family. As they navigate the trails, the boys exhibit their scouting skills and tease one another amid their journey, setting a light-hearted tone. The camaraderie, humor, and adventures hint at the themes of resilience and teamwork, inviting readers to join the Scouts in their quests and experiences that promise more excitement ahead. (This is an automatically generated summary.)s
Release date is 2014-05-17
E-text prepared by Stephen Hutcheson, Rod Crawford, Dave Morgan, and the Online Distributed Proofreading Team (http://www.pgdp.net)
Keywords: Boy Scouts -- Juvenile fiction; Floods -- Juvenile fiction; Susquehanna River -- Juvenile fiction